The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0168297
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Air Pollutants during Two Distinct Episodes of Fireworks Burning in a Valley City of North China

Abstract: BackgroundThe elevation and dissipation of pollutants after the ignition of fireworks in different functional areas of a valley city were investigated.MethodsThe Air Quality Index (AQI) as well as inter-day and intra-day concentrations of various air pollutants (PM10, PM2.5, SO2, NO2, CO, O3) were measured during two episodes that took place during Chinese New Year festivities.ResultsFor the special terrain of Jinan, the mean concentrations of pollutants increased sharply within 2–4 h of the firework displays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…It is argued that air quality gets worse in the aftermath of Diwali, on account of firecrackers that get burned during the festival. The link between firecracker burning and air pollution has been established in other regions (for example, [ 5 ]). This has resulted in calls for banning the sale of firecrackers, and in 2017, the Supreme Court of India did order such a ban.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that air quality gets worse in the aftermath of Diwali, on account of firecrackers that get burned during the festival. The link between firecracker burning and air pollution has been established in other regions (for example, [ 5 ]). This has resulted in calls for banning the sale of firecrackers, and in 2017, the Supreme Court of India did order such a ban.…”
Section: Introductionmentioning
confidence: 99%
“…In USA, short-term increases in PM concentrations as well as its constituents have been reported during the Independence Day (July 4 th ) fireworks (Wang et al, 2012), and in one analysis, several stations were found to exceed the 24h National Ambient Air Quality Standard [NAAQS] for PM2.5 (35 µg/m 3 ) during the event (Seidel and Birnbaum, 2015). Similarly, in China, a number of studies have reported significant elevation in pollutant concentrations during Chinese New Year activities (Carranza et al, 2001;Han et al, 2014;Lai and Brimblecombe, 2017;Li et al, 2017;Li et al, 2013;Shi et al, 2014;Song et al, 2017). Wang et al (2007) (Ambade, 2018;Barman et al, 2008;Gautam et al, 2018;Kumar et al, 2016a;Rao et al, 2012;Yerramsetti et al, 2013).…”
Section: Air Quality During Firework Eventsmentioning
confidence: 99%
“…Analysis of the simultaneous characteristics of these six air pollutants can help the public, scientists and policy makers gain a comprehensive understanding of the air quality. Some studies have evaluated air quality according to CAAQS [29,30]. Ji et al conducted an analysis of two regional events in northern China between October and November 2009, using PM 10 , SO 2 and NO x data collected in 24 monitoring sites [30].…”
Section: Introductionmentioning
confidence: 99%
“…Ji et al conducted an analysis of two regional events in northern China between October and November 2009, using PM 10 , SO 2 and NO x data collected in 24 monitoring sites [30]. Song et al measured the Air Quality Index (AQI), as well as concentration of various air pollutants (PM 10 , PM 2.5 , SO 2 , NO 2 , CO, O 3 ) during two episodes of Chinese New Year festivities in the city of Jinan [29]. However, due to the lack of high spatial-temporal resolution data (most monitoring site in China began collecting air pollutant data in January 2014, whereas some cities such as Putian and Nangping began collecting data in January 2015), not many studies have focused on all the six criteria air pollutants.…”
Section: Introductionmentioning
confidence: 99%